2017
DOI: 10.1039/c7tb00479f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles/thermosensitive hydrogel reinforced with chitin whiskers as a wound dressing for treating chronic wounds

Abstract: Nanoparticles/thermosensitive hydrogel reinforced with chitin whiskers as a wound dressing for treating chronic wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…Then, the positively charged amino group can directly attack the negatively charged bacterial cell membrane via electrostatic attraction to disrupt the cell membrane to achieve a good antibacterial effect, which differs from target-specific interactions of conventional antibiotics and prevents drug resistance of bacteria from occurring to some extent [15][16][17]. By now, some CS-based wound dressing products have been developed in dosage forms of hydrogel [18,19], film [9], and sponge [20], among which hydrogel or hydrogel film is able to provide a moist environment to the wound, effectively preventing tissue dehydration and cell death, enhancing the migration of inflammatory cells and growth factors, facilitating air exchange and angiogenesis, serving as a microbial barrier, removing excessive exudate, and accelerating wound healing, among other merits, and thus has good application prospect [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the positively charged amino group can directly attack the negatively charged bacterial cell membrane via electrostatic attraction to disrupt the cell membrane to achieve a good antibacterial effect, which differs from target-specific interactions of conventional antibiotics and prevents drug resistance of bacteria from occurring to some extent [15][16][17]. By now, some CS-based wound dressing products have been developed in dosage forms of hydrogel [18,19], film [9], and sponge [20], among which hydrogel or hydrogel film is able to provide a moist environment to the wound, effectively preventing tissue dehydration and cell death, enhancing the migration of inflammatory cells and growth factors, facilitating air exchange and angiogenesis, serving as a microbial barrier, removing excessive exudate, and accelerating wound healing, among other merits, and thus has good application prospect [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the drug loading of BSA in hydrogels could be completed with high efficiency. The thermosensitive HBC hydrogels have been developed and applied in the delivery of many kinds of drugs, such as 5‐FU (0.13 kDa), dexamethasone sodium phosphate (0.39 kDa), doxorubicine hydrochloride (0.58 kDa), linezolid (0.33 kDa), insulin (5.80 kDa), and bovine serum albumin (66.43 kDa). These reports indicated that the thermosensitive HBC‐based hydrogels could load soluble drugs easily and high‐efficiently with a wide range of molecular weights ranging from 0.13 to 66.43 kDa, which could be a potential drug delivery platform.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular and immunological entrapment into the wound is commonly categorized into three main phases for wound restoration 1 (inflammation, proliferation and remodelling). Chronic wounds are recognized by the deterioration in their wound healing process leading to putrefaction, infection or even resection 2 . The typical properties of the wound treating material includes having an anti-infective effect 3 , therefore, it is intended to use antimicrobial agents loaded onto nanomaterials for enhancing the wound recovery rate with controlled release and high penetration power.…”
Section: Introductionmentioning
confidence: 99%